RANCANG BANGUN PENDETEKSI KEBOCORAN GAS LPG DENGAN SENSOR MQ-5 BERBASIS ARDUINO UNO - Muawan Bisri; Lukman Hakim; Okto Kurnia (LPPM UNIVERSITAS BINA INSAN, 2026)
Liquefied Petroleum Gas (LPG) leakage is one of the leading causes of fires and explosions in residential and commercial environments. The inability to detect gas leaks quickly and accurately can increase the risk of accidents, property damage, and loss of life. This study aims to design and implement an LPG gas leakage detection system using an MQ-5 gas sensor based on an Arduino Uno microcontroller. The research employed the Prototype method, which consists of requirements analysis, prototype design, prototype testing, program coding, system testing, and device implementation. The MQ-5 sensor was utilized to detect LPG gas concentration and classify leakage levels into three categories: safe at concentrations below 300 ppm, warning at concentrations ranging from 300 to 700 ppm, and danger at concentrations above 700 ppm, while the Arduino Uno served as the main controller for processing sensor data. The system was equipped with an LCD to display gas concentration, a buzzer as an audible warning device, and a GSM SIM800L module to automatically send SMS notifications when a gas leak was detected. The testing results demonstrated that the proposed system was able to accurately detect LPG gas leakage and provide early warnings through both audible alarms and SMS notifications. Therefore, the developed system can enhance safety and minimize the risk of fires caused by LPG gas leakage by providing real-time monitoring and multi-level risk classification.